Lactational Changes of Phospholipids Content and Composition in Chinese Breast Milk - Yang, Meng-Tao; Lan, Qiu-Ye; Liang, Xue; Mao, Ying-Yi; Cai, Xiao-Kun; Tian, Fang; Liu, Zhao-Yan; Li, Xiang; Zhao, Yan-Rong; Zhu, Hui-Lian (Nutrients, 2022)
Phospholipids are pivotal polar lipids in human milk and essential for infants’ growth and development, especially in the brain and cognitive development. Its content and composition are affected by multiple factors and there exist discrepancies in different studies. In this study, we determined five major phospholipids classes (phosphatidylethanolamine, phosphatidylinositol, phosphatidylserine, phosphatidylcholine, and sphingomyelin) in 2270 human milk samples collected from 0 to 400 days postpartum in six regions of China. The high-performance liquid chromatography coupled with an evaporative light scattering detector (HPLC-ELSD) was performed to quantify the phospholipids. Total phospholipid median (IQR) content was in a range between 170.38 ± 96.52 mg/L to 195.69 ± 81.80 mg/L during lactation and was higher concentrated in colostrum milk and later stage of lactation (after 200 days postpartum) compared with that in the samples collected between 10 to 45 days postpartum. Variations in five major sub-class phospholipids content were also observed across lactation stages (phosphatidylethanolamine: 52.61 ± 29.05 to 59.95 ± 41.74 mg/L; phosphatidylinositol: 17.65 ± 10.68 to 20.38 ± 8.55 mg/L; phosphatidylserine: 15.98 ± 9.02 to 22.77 ± 11.17 mg/L; phosphatidylcholine: 34.13 ± 25.33 to 48.64 ± 19.73 mg/L; sphingomyelin: 41.35 ± 20.31 to 54.79 ± 35.26 mg/L). Phosphatidylethanolamine (29.18–32.52%), phosphatidylcholine (19.90–25.04%) and sphingomyelin (22.39–29.17%) were the dominant sub-class phospholipids in Chinese breast milk during the whole lactation period. These results updated phospholipids data in Chinese human milk and could provide evidence for better development of secure and effective human milk surrogates for infants without access to breast milk.